Cytokines expression in primary and non-primary maternal cytomegalovirus (CMV) infection - Faizal, Nur Fazlin Akmal Muhammad (2022)
Cytomegalovirus (CMV) infection in pregnancy is the commonest cause of congenital infection worldwide. Primary CMV infection in pregnancy carries a higher risk of fetal transmission compared to non-primary infection. Primary infection in the early trimester of pregnancy can cause serious complications such as miscarriages and severe congenital malformations. CMV infection changes Th1 and Th2 balance during pregnancy by altered cytokine (IL-8, IL-6) in placental cells. Thus, this study aims to determine the cytokines expression in primary and nonprimary maternal CMV infections and to compare the expression of cytokines in both types of infection. This cross-sectional study was conducted at Microbiology Laboratory, Hospital Universiti Sains Malaysia (HUSM) from June 2019 until July 2020. The result of this study showed that seventy-four pregnant women with abnormal pregnancy outcomes with positive CMV IgG with or without IgM were subjected to IgG avidity assay by electrochemiluminiscence immunoassay (ECLIA) method to discriminate primary and non-primary CMV infection. Then, study also showed sera of the patients in primary and non-primary CMV infection were subjected to multiplex cytokine assay for cytokine analysis that involved seven cytokines and two chemokines to determine their concentrations in both primary and non-primary CMV infection. Cytokines and chemokines tested were IL-12, IL-2, IFN- γ, TNF-α, IL-1β, IL-6, IL-10, IFN- γ, TNF-α, MCP-1 (CCL-2), and IFN- γ IP- 10 (CXCL-10). Concentrations of IL-1β, IL-6, and MCP-1 (CCL-2) were significantly elevated in pregnant women with primary CMV infection. The intensity Cytomegalovirus (CMV) infection in pregnancy is the commonest cause of congenital infection worldwide. Primary CMV infection in pregnancy carries a higher risk of fetal transmission compared to non-primary infection. Primary infection in the early trimester of pregnancy can cause serious complications such as miscarriages and severe congenital malformations. CMV infection changes Th1 and Th2 balance during pregnancy by altered cytokine (IL-8, IL-6) in placental cells. Thus, this study aims to determine the cytokines expression in primary and nonprimary maternal CMV infections and to compare the expression of cytokines in both types of infection. This cross-sectional study was conducted at Microbiology Laboratory, Hospital Universiti Sains Malaysia (HUSM) from June 2019 until July 2020. The result of this study showed that seventy-four pregnant women with abnormal pregnancy outcomes with positive CMV IgG with or without IgM were subjected to IgG avidity assay by electrochemiluminiscence immunoassay (ECLIA) method to discriminate primary and non-primary CMV infection. Then, study also showed sera of the patients in primary and non-primary CMV infection were subjected to multiplex cytokine assay for cytokine analysis that involved seven cytokines and two chemokines to determine their concentrations in both primary and non-primary CMV infection. Cytokines and chemokines tested were IL-12, IL-2, IFN- γ, TNF-α, IL-1β, IL-6, IL-10, IFN- γ, TNF-α, MCP-1 (CCL-2), and IFN- γ IP- 10 (CXCL-10). Concentrations of IL-1β, IL-6, and MCP-1 (CCL-2) were significantly elevated in pregnant women with primary CMV infection. The intensity of IFN-γ, IL-12, and IL-2 was higher in primary CMV infection compared to nonprimary CMV infection. The productions of pro-inflammatory cytokine together with MCP-1 (CCL-2) in pregnant women with primary CMV infection were significant, which showed the predominance of Th1 response. The low level of cytokines in nonprimary CMV infection might be due to the latent state of CMV in a host. Thus, it does not trigger the immune host cells' reactivation.